2014
DOI: 10.1590/s0103-05822014000400016
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a virtual reality-based intervention on motor performance and balance of a child with cerebral palsy: a case study

Abstract: Objective: To verify the effect of an intervention protocol using virtual reality (VR) on the motor performance and balance of a child with cerebral palsy (CP). Case description: To comply with the proposed objectives, a 7-year old child with spastic hemiplegic cerebral palsy (CP), GMFCS level I, was submitted to a physiotherapy intervention protocol of 12 45-minute sessions, twice a week, using virtual reality-based therapy. The protocol used a commercially-available console (XBOX®360 Kinect ® ) able to track… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 24 publications
0
9
0
5
Order By: Relevance
“…Other applications of this device are in the area of agronomy, education, cartography, and robotics [ 36 , 37 ]. Studies utilizing virtual reality (VR) systems for improving the functional skills of the upper limbs have shown the Kinect platform to be a promising rehabilitation tool for CP treatments [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. In this context, Microsoft Kinect v2 (Microsoft, Redmond, WA, USA) is an RGB-D depth sensor that uses a grid of infrared light.…”
Section: Introductionmentioning
confidence: 99%
“…Other applications of this device are in the area of agronomy, education, cartography, and robotics [ 36 , 37 ]. Studies utilizing virtual reality (VR) systems for improving the functional skills of the upper limbs have shown the Kinect platform to be a promising rehabilitation tool for CP treatments [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. In this context, Microsoft Kinect v2 (Microsoft, Redmond, WA, USA) is an RGB-D depth sensor that uses a grid of infrared light.…”
Section: Introductionmentioning
confidence: 99%
“…Unilateral spastic CP, or hemiplegia, is the most common subtype, representing 35-40% of new diagnoses (4,5). Children with hemiplegia have motor, cognitive, sensory and perceptual challenges that limit postural control and activities of daily living, reducing functional independence (6)(7)(8)(9)(10). Assisting children to learn new motor skills, improve existing skills, and transfer skills to enhanced function in the real world is a primary goal of rehabilitation (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…A case study developed by Peacock et al [19], in which virtual reality has been used as an intervention for a child with cerebral palsy; it was found that there were gains on the motor performance, functional balance and mobility of this child based in Motor Development Scale (MDS) with gains in all areas evaluated, except in spatial organization. There was also an increase in the child's scores on the Pediatric Balance Scale (PBS) reaching maximum score after the intervention.…”
Section: Introductionmentioning
confidence: 99%